From Meerkat to Periscope: Does Intellectual Property Law Prohibit the Live Streaming of Commercial Sporting Events? - Edelman, Marc (The Columbia Journal of Law & the Arts, 2016)
On February 27, 2015, San Francisco entrepreneur Ben Rubin announced the launch of his live streaming video application, Meerkat. Named after “the cute but carnivorous mongoose native to Africa,” Meerkat allows users to upload video footage from smartphones to the Internet for worldwide, instantaneous viewing. In the weeks following Meerkat’s launch, Twitter unveiled a similar online application, Periscope, which allows users to watch live videos for up to twenty-four hours after their initial broadcast. Twitter’s more recent entry into the live streaming market has enhanced the credibility of this new technology. Furthermore, it has placed live streaming on the radar of major private equity firms. Although the American business community generally characterizes live streaming as a favorable technological development, the use of live streaming technologies to broadcast (or rebroadcast) commercial sporting events is more controversial. According to one sports network analyst, the advent of live streaming could potentially result in a “Napster-type thing” involving mass infringement of sports enterprises’ intellectual property rights. Another sports industry expert cautioned that “[t]his kind of technology is going to have huge [negative] implications for broadcasters like NBC, which has already paid billions for the Olympics.” This Article discusses the potential impact of live streaming on the commercial sports industry and analyzes whether commercial sports enterprises have the legal power to stop live streaming of professional and collegiate sporting events. Part I of this Article explores the history of live streaming commercial sporting events. Part II analyzes whether courts are likely to hold live streamers directly liable for their actions under federal copyright law. Part III discusses whether courts are likely to hold manufacturers of live streaming applications secondarily liable for copyright infringement. Part IV assesses the legality of live streaming under right of publicity law. Part V then analyzes the legality of live streaming under unfair competition doctrines. Finally, Part VI concludes that current federal and state laws adequately address all meaningful public policy concerns related to the live steaming of commercial sporting events.